HTLV Screening of Blood Donations in England Between 2002 and 2021-Comparison of Screening Strategies - Harvala, Heli; Davison, Katy; Webster, Mhairi; Reynolds, Claire; Taylor, Graham P. (OXFORD UNIV PRESS INC, 2025)
Background. Human T-lymphotropic virus (HTLV) is associated with adult T-cell leukemia/lymphoma and myelopathy. Here we present virological and epidemiological data on HTLV screening of blood donations in England between 2002 and 2021, implemented to prevent its transmission via blood transfusion.
Methods. Data on HTLV testing of blood donations was reviewed; it was initially conducted in pools (2002-2012) and subsequently using individual samples (all donors, 2013-2016; first-time donors and non-leucodepleted component donors, 2017-2021). Data included annual number of donations screened, initial and repeat reactives as well as confirmed positives. Further information, such as likely source of infection, was obtained for HTLV-positives.
Results. Over the 20-year study period, a total of 30 679 741 blood donations were screened for HTLV in England. Under pooled screening strategy, the annual rate of repeat reactive donations remained <5:100 000. However, this rate increased to 51:100 000 with individual screening and further to 123:100 000 with selective screening. A total of 5032 samples were repeat reactive, of which 278 were confirmed HTLV-positives. Although the specificity under each scenario exceeded 99.9%, the rate of repeat reactives was around 50-fold higher in individual compared to pooled screening. Most HTLV infected were UK-born, most likely acquired their infection unknowingly through breast feeding or heterosexual intercourse with an individual associated with an HTLV-endemic country.
Conclusions. These data highlight that pooled testing can be advantageous in low-prevalence settings due to its high specificity and reduced non-specific reactivity. Whether pooling is an applicable strategy to tackle the burden of HTLV infection in resource-poor, HTLV-endemic countries requires further investigations.